Experimental studies on mix design and properties of ceramic-glass geopolymer mortars using response surface methodology - Meysam Pourabbas Bilondi; Vahideh Ghaffarian; Mahdi Amiri Daluee; Reyhaneh Pakizehrooh; Saeed Hosseini Tazik; Alireza Behzadian; Mojtaba Zaresefat (Scientific Reports)
Abstract This study explores the mechanical properties of geopolymer mortars incorporating ceramic and glass powders sourced from industrial waste. A Box-Behnken design was employed to assess the effects of ceramic waste powder (CWP) content, alkaline activator ratio, solution-to-binder (S: B) ratio, and oven curing duration on the mortar’s performance. Compressive strengths were measured at 3 and 28 days, and regression models were developed to predict these outcomes. The relationships between compressive strength, flexural strength, and ultrasonic pulse velocity (UPV) were also analyzed. Microstructural and molecular changes were investigated using scanning electron microscopy and fourier transform infrared spectroscopy. According to response surface methodology results, the maximum compressive strengths of 22.79 MPa at three days and 25 MPa at 28 days were achieved using a mix containing 85.8% CWP, a 1.02 sodium hydroxide (NH): sodium silicate (NS) ratio, a 0.647 S: B ratio, and a 12-h oven curing time. Optimal oven curing conditions resulted in 28-day compressive strength, flexural strength, and UPV values of 25.7 MPa, 5.62 MPa, and 5765 m/s, respectively. .